2022-RA-1102-ESGO A comparison of end-to-end and end-to-side anastomosis following rectosigmoid resection in ovarian cancer cytoreductive surgery. (20th October 2022) - Graham, Radha; Kotsopoulos, Ioannis
Abstract : Introduction/Background: Rectosigmoid resections are performed commonly during cytoreductive surgery for ovarian cancer. The two most common approaches to reconstruction are end-to-end (EE) and end-to-side (ES) anastomosis. Data from colorectal studies, including a meta-analysis of randomised controlled trials, suggest a significantly lower anastomotic leak rate following end-to-side compared to end-to-end anastomosis. Here we present the experience from a single gynaecological oncology centre. Methodology: Retrospective data regarding surgery was collected from electronic records for all patients who underwent primary cytoreductive surgery for stage III/IV ovarian cancer during the study period. Results: Over a period of 51 months (01/01/2018–01/04/2022), 243 cytoreductive surgeries were undertaken. A recto-sigmoid resection was performed in 80 (32.9%) patients. Fifteen (18.8%) patients had an end colostomy and five (6.3%) an end ileostomy following total colectomy. A reconstruction with an end-to-end anastomosis was undertaken in 34 (42.5%) patients, and an end-to-side anastomosis in 26 (32.5%). The rate of defunctioning ileostomy was 4 (15.4%) in the ES group and 12 (35.3%) in the EE group and was not significantly different between the two groups. There were two cases (5.9%) of anastomotic leak in the EE group, and no leaks in the ES group. Both leaks were small, and successfully conservatively managed. There was no statistically significant difference in leak rate found between the two groups. Conclusion: This study reports successful implementation of the end-to-side anastomosis technique in ovarian cancer cytoreductive surgery. Additional prospective randomised trials, specifically focussed in this group, are warranted.